Oral Administration of Si-Based Agent Attenuates Oxidative Stress and Ischemia-Reperfusion Injury in a Rat Model: A Novel Hydrogen Administration Method - Kawamura, Masataka; Imamura, Ryoichi; Kobayashi, Yuki; Taniguchi, Ayumu; Nakazawa, Shigeaki; Kato, Taigo; Namba-Hamano, Tomoko; Abe, Toyofumi; Uemura, Motohide; Kobayashi, Hikaru; Nonomura, Norio (Frontiers in Medicine, 2020)
Organ ischemia-reperfusion injury (IRI), which is unavoidable in kidney transplantation, induces the formation of reactive oxygen species and causes organ damage. Although the efficacy of molecular hydrogen (H2) in IRI has been reported, oral intake of H2-rich water and inhalation of H2 gas are still not widely used in clinical settings because of the lack of efficiency and difficulty in handling. We successfully generated large quantities of H2 molecules by crushing silicon (Si) to nano-sized Si particles (nano-Si) which were allowed to react with water. The nano-Si or relatively large-sized Si particles (large-Si) were orally administered to rats with renal IRI. Animals were divided into four groups: sham, IRI, IRI + nano-Si, and IRI + large-Si. The levels of serum creatinine and urine protein were significantly decreased 72 h following IRI in rats that were administered nano-Si. The levels of　oxidative stress marker, urinary 8-hydroxydeoxyguanosine were also significantly decreased with the nano-Si treatment. Transcriptome and gene ontology enrichment analyses showed that the oral nano-Si intake downregulated the biological processes related to oxidative stress, such as immune response, cytokine production, and extrinsic apoptotic signaling pathway. Alterations in the regulation of a subset of genes in the altered pathways were validated by quantitative polymerase chain reaction. Furthermore, immunohistochemical analysis demonstrated that the nano-Si treatment alleviated interstitial macrophage infiltration and tubular apoptosis, implicating the anti-inflammatory and anti-apoptotic effects of nano-Si. In conclusion, renal IRI was attenuated by the oral administration of nano-Si, which should be considered as a novel H2 administration method.